Dietary Iron Intake and Anemia Are Weakly Associated, Limiting Effective Iron Fortification Strategies in India. Issue 5 (3rd May 2019) - Swaminathan, Sumathi; Ghosh, Santu; Varghese, Jithin Sam; Sachdev, Harshpal S; Kurpad, Anura V; Thomas, Tinku
ABSTRACT: Background: Anemia prevalence in India remains high despite preventive iron supplementation programs. Consequently, concurrent national policies of iron fortification of staple foods have been initiated. Objectives: This study evaluated the relation between dietary iron intake and anemia (hemoglobin <12 g/dL) in women of reproductive age (WRA; 15–49 y) with respect to iron fortification in India. Methods: Data from 2 national surveys were used. Data on hemoglobin in WRA were sourced from the National Family Health Survey-4, whereas dietary intakes were sourced from the National Sample Survey. Adjusted odds for anemia with increasing iron intake were estimated, along with the effect of modulating nutrients such as vitamins B-12 and C, from statistically matched household data from the 2 surveys. The risks of inadequate (less than the Estimated Average Requirement for WRA) and excess (more than the tolerable upper limit for WRA) intakes of iron were estimated by the probability approach. Results: The relation between iron intake and the odds of anemia was weak (OR: 0.992; 95% CI: 0.991, 0.994); increasing iron intake by 10 mg/d reduced the odds of anemia by 8%. Phytate and vitamin B-12 and C intakes modified this relation by reducing the odds by 1.5% when vitamin B-12 and C intakes were set at 2 μg/d and 40 mg/d, respectively. The additional intake of 10 mg/d of fortified iron reduced the risk of dietary iron inadequacy from 24–94% to 9–39% across states, with no risk of excess iron intake. Approximately doubling this additional iron intake reduced the risk of inadequacy to 2–12%, but the risk of excess intake reached 22%. Conclusions: Providing fortified iron alone may not result in substantial anemia reduction among WRA in India and could have variable benefits and risks across states. Geographically nuanced dietary strategies that include limited fortification and the intake of other beneficial nutrients should be carefully considered.